Effect of external air-conditioner units' heat release modes and positions on energy consumption in large public buildings. (January 2017) - Han, Mengtao; Chen, Hong
Abstract: The heat released from the air-conditioners of large public buildings, which has long-term and far-reaching influences, not only changes the thermal environment surrounding the buildings but also profoundly impacts the air-conditioner energy consumption. In this paper, a quantitative evaluation of the impact of the heat release modes and positions of air-conditioner external units on both the environment surrounding the buildings and the air-conditioner energy consumption of large public buildings is conducted using a coupled simulation of convection, radiation and conduction and air-conditioner energy cost. Principles for external unit positions are explored as well. Highlights: Air-conditioner heat release feeds back to interior by ventilation and infiltration, increasing energy consumption. Different positions of external units will lead to different energy consumption addition. Fan-cooled sensible heat release will increase the air temperature around building and the energy consumption for cooling. Cooling tower tremendously increases the humidity around the building and the energy consumption for dehumidification. Heat release from cooling tower results in much more energy consumption than that of VRV in cooling and dehumidification.